1981
DOI: 10.1159/000232772
|View full text |Cite
|
Sign up to set email alerts
|

Orally Induced Tolerance

Abstract: Several elements of the phenomenon of oral tolerance were examined. It was shown that whereas intragastric (i.g.) exposure of mice to the T-dependent antigens oval-bumin (OVA), bovine serum albumin, and human gamma globulin severely compromised the ability to respond to a subsequent challenge with the homologous antigen, i.g. treatment with T-independent antigens such as dinitrophenylated Ficoll, polyvinylpyrrolidone and bacterial lipopolysaccharide (LPS) did not induce anergy. Furthermore, mice parenterally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…This route of antigen administration can lead to immunity or tolerance, depending on the dose, number of feedings, and the form of antigen used (15). T-dependent, but not T-independent, antigens can lead to the induction of oral tolerance (16), and the immune response to collagen is T dependent (17,18). The studies reported here show that intragastric administration of soluble type II collagen suppresses the induction of CIA in mice.…”
mentioning
confidence: 78%
“…This route of antigen administration can lead to immunity or tolerance, depending on the dose, number of feedings, and the form of antigen used (15). T-dependent, but not T-independent, antigens can lead to the induction of oral tolerance (16), and the immune response to collagen is T dependent (17,18). The studies reported here show that intragastric administration of soluble type II collagen suppresses the induction of CIA in mice.…”
mentioning
confidence: 78%
“…This finding is especially important since (i) oral tolerance, to be broadly applicable, must be effective in situations where potentially pathogenic lymphocytes exist and (ii) conventional oral tolerization protocols are less efficient at suppressing immune responses in systematically immune animals than in naive animals (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, unless tolerogens are administered repeatedly and in large doses, tolerance is usually modest and of short duration (17,18), being rather difficult to induce in an already-immune host (19)(20)(21)(22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, however, requires administration of massive amounts of antigens or prolonged feeding of small amounts of antigens, which are then only effective in rather narrow dose ranges. Further, oral tolerance is especially difficult to induce in an already immunologically sensitized host (14)(15)(16)(17)(18), such as in patients harboring autoreactive T cells.…”
mentioning
confidence: 99%